Ultramorphological changes in gill rakers of Astyanax altiparanae (Characidae) kept in contaminated environments - Lopes, F. P. [UNESP]; Pereira, B. F.; Alves, R. M.S. [UNESP]; Valim, J. R.T. [UNESP]; Figueiredo, F. A.T.; Pitol, D. L.; Caetano, F. H. [UNESP] (Springer Nature, 2017)
Most water bodies in Brazil, and in the world, are contaminated by some types of pollutants, ranging from sewage to metal/chemicals, carcinogenic products, and biodegradable detergents. Despite the extensive knowledge on their effects on fish biology and especially on gill morphology, research that concerns their impacts on gill rakers and implications in parameters such as food consumption cannot be found in the literature. Gill rakers are vital because, together with gills, they are responsible for the defense and protection of the organism and for selecting appropriate food for survival. When detergents, which can act as toxic chemical agents, get in contact with the body of the fish, they can cause severe effects that must be understood. Therefore, our study investigated ultramorphological changes in gill rakers of Astyanax altiparanae (Lambeth) caused by the exposure to biodegradable detergents. Fish were exposed to a 1 mg/L dilution of a mixture of detergents and pure water from an artesian well for 5 months. Results revealed that the first month of exposure to detergent caused dilation of chemical receptors in taste buds and the rise of a large number of orifices for mucus release among pavement cells in gill rakers, although only a small amount of mucus was found in fish exposed both to pure water and the detergent dilution. After 5 months, there was an increase in the dilation of these chemoreceptors, excess mucus on gill rakers of detergent groups, and the emergence of microbridges between microridges in pavement cells.
Keywords: Chemical receptors; Microbridges; Mucus; Taste buds